Torpor in three species of Brazilian hummingbirds under semi-natural conditions - Bech, C.; Abe, Augusto Shinya [UNESP]; Steffensen, J. F.; Berger, M.; Bicudo, J. E. P. W. (Cooper Ornithological Soc, 1997)
We measured body temperatures in three species of Brazilian hummingbirds, the Versicolored Emerald (Amazilia versicolor; body mass 4.1 g), the Black Jacobin (Me lantrochilus fuscus; body mass 7.7 g) and the Swallow-tailed Hummingbird (Eupetomena macroura; body mass 8.6 g), during overnight exposure to natural conditions of photoperiod and ambient temperatures. All three species entered torpor. In both A. versicolor and E. macroura, individuals entered torpor even if they had access to feeders up to the time of sunset. In contrast, M. fuscus was less prone to enter torpor and did so mainly if it had been fasting for more than two hours before sunset. Furthermore, M. fuscus often spent the whole night in torpor, whereas the two other species entered torpor for a variable, often short, period of the night. We observed more than one torpor bout during a single night in all three species. We suggest that multiple nocturnal torpors result from interruption of the normal torpor pattern by some (unknown) external stimuli. Any interrupted torpor was always followed by a new entry into torpor, supporting the view that there is a body mass threshold below which the hummingbirds must enter torpor Our data also indicate that these hummingbird species might use torpor even if they are not energetically stressed.
Keywords: hummingbirds; Amazilia versicolor; Melanotrochilus fuscus; Eupetomena macroura; torpor; thermoregulation; body temperature